AMF enhance secondary metabolite production in ashwagandha, licorice, and marigold in a fungi-host specific manner - Johny, Leena; Cahill, David M.; Adholeya, Alok (Rhizosphere, 2021)
Strategies to enhance the production of secondary metabolites, derived from medicinal and agriculturally important plants have been the subject of exploration to enable effective utilization of these biorepositories. Through symbiosis, arbuscular mycorrhizal fungi (AMF), modify plant primary and secondary metabolite biosynthesis. The relationship thus offers the opportunity to exploit combinations of host and fungus that maximize secondary metabolite production. We investigated different AMF host combinations for the enhancement of root-derived secondary metabolites from three plant species - ashwagandha (Withania somnifera (L.) Dunal), licorice (Glycyrrhiza glabra L.), and marigold (Tagetes erecta L.). Each host species was inoculated singly with each of five species of AMF, Glomus hoi, Claroideoglomus etunicatum, Claroideoglomus claroideum, Rhizophagus irregularis, and Acaulospora delicata and secondary metabolite production was assessed. Increased concentrations of the following secondary metabolites were found in roots after AMF establishment: for withaferin-A in ashwagandha (concentrations ranged from 11.5 to 43.5% above than in control non-mycorrhized roots depending on the host and AMF combination); in licorice, glycyrrhizic acid (1.51–3.92% above control) and glabridin (2.85–6.41% above control) and in marigold, alpha-terthienyl (1.51–7.18% above control). Specifically, among the AMF inoculations, the highest levels of secondary metabolite were found in ashwagandha and marigold inoculated with R. irregularis and for licorice following inoculation with C. etunicatum revealing the impact of different AMF species on different plant species. This underpinning knowledge of AMF symbioses with the plant host will augment the development of methods that will provide enhanced concentrations of secondary metabolites of commercial value. •Inoculation of AMF improved secondary metabolite production in the host plants.•Ashwagandha and marigold showed maximum secondary metabolites production with Rhizophagus irregularis inoculation.•Licorice showed maximum secondary metabolites production with Claroideoglomus etunicatum inoculation.